The answer to this question depends on what method you are supposed to use. If a, b, and c are sides of a triangle, use the Pythagorean Theorem: C^2 = A^2 + B^2, C^2 = 25+49, C^2 = 74, C = 74^1/2 (or the square root of 74).
If you are following a pattern and A = 5, B = 7, then C may = 9.
It all depends on the context of the question.
a + c - b = 3 + 2 - 5 = 5 - 5 = 0
If a = -15, b = 5 and c = -2 a - b - c = -15 - 5 - (-2) = -20 + 2 = -18
ac is 7 if b is 3 and a is 2 a nd c is 5
4
The -7 is called the difference. In any subtraction problem: a = b - c a is the difference b and c are terms (technically, b is minuend and c is subtrahend, but these terms are not really used in modern math)
the answer is a
a + c - b = 3 + 2 - 5 = 5 - 5 = 0
If a = -15, b = 5 and c = -2 a - b - c = -15 - 5 - (-2) = -20 + 2 = -18
ac is 7 if b is 3 and a is 2 a nd c is 5
4
The -7 is called the difference. In any subtraction problem: a = b - c a is the difference b and c are terms (technically, b is minuend and c is subtrahend, but these terms are not really used in modern math)
Z if d is equally to f plus10
To find this: You know (B+C) = 7. Therefore you know (A+A )= 21 - (B+C). Therefore 21-7 = 14. So now you know (A+A) = 14. So you divide (A+A)/2. This equals 7. Therefore A = 7.
Well, isn't that just a happy little math problem! If A is less than B and B plus C equals 10, then it must be true that A plus C is less than 10. Just remember, in the world of numbers, everything adds up beautifully in the end.
6 + 12 - 5 = 13
If any number B is subtracted from a number A to give C, then C+B =A If A - B = C then B+C = A Eg 7 - 2 = 5 Hence 2 + 5 = 7
a - b = c -(a - b) = -c b - a = -c